PENGARUH KETIDAKTEPATWAKTUAN PELAPORAN KEUANGAN BERPENGARUH PADA REAKSI PASARPERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2016-2017 - I Gusti Ayu Ratih Permata Dewi; Putu Yudha Asteria Putri; Putu Diah Putri Idawati (KRISNA: Kumpulan Riset Akuntansi, 2019)
This study aims to determine the effect of profitability and firm size on the timeliness of financial reporting, and to determine the effect of financial reporting inaccuracies on market reactions. The population in this study are manufacturing companies listed on the Indonesia Stock Exchange during the period 2016-2017. By using purposive sampling in the selection of samples, obtained as many as 40 listed companies which until April 1, 2013 have not submitted audited financial statements that expire on December 31, 2016-2017. The data analysis technique used in this study is multiple regression analysis. The results of this study prove that the profitability and size of the company influences the inaccuracy of financial reporting, while the imprecision of financial reporting does not affect the market reaction of manufacturing companies listed on the Indonesia Stock Exchange during the period 2016-2017.